Impact Evaluation of Cash, Food Vouchers, and Food Transfers among Colombian Refugees and Poor Ecuadorians in Carchi and Sucumbios: Endline Survey - International Food Policy Research Institute; Centro de Estudios de Pobalcion y Desarrollo Social; World Food Programme (International Food Policy Research Institute, 2015)
In April 2011, the World Food Program (WFP) expanded its assistance to address the food security and nutrition needs of Colombian refugees and to support their integration into Ecuadorian communities. The new program was designed as a prospective randomized control trial and consisted of six monthly transfers of cash, food vouchers, or food to Colombian refugees and poor Ecuadorian households. The objectives of the program were three-fold: 1) to improve food consumption by facilitating access to more nutritious foods, 2) to increase the role of women in household decision-making related to food consumption, and 3) to reduce tensions between Colombian refugees and host Ecuadorian populations. The program was implemented in seven urban centers in the provinces of Carchi and Sucumbíos. IFPRI conducted an impact evaluation targeted at estimating the relative impact and cost-effectiveness of cash, food vouchers, and food transfers on household food security indicators; as well as complimentary indicators such as household expenditure and female status.